Non‐alcoholic fatty liver disease independently predicts prediabetes during a 7‐year prospective follow‐up. (8th May 2013) - Zelber‐Sagi, Shira; Lotan, Roni; Shibolet, Oren; Webb, Muriel; Buch, Assaf; Nitzan‐Kaluski, Dorit; Halpern, Zamir; Santo, Erwin; Oren, Ran
Abstract: Background & Aims: Non‐alcoholic fatty liver disease (NAFLD) is suspected to confer an increased risk for developing type 2 diabetes (DM). However, only a few prospective studies evaluated NAFLD as a predictor for DM, most did not adjust for the full range of potential cofounders and none used an objectively quantified degree of steatosis. Our aim was to evaluate the independent role of NAFLD in predicting the development of pre‐DM in a 7‐year prospective follow‐up of healthy volunteers. Methods: A prospective cohort of a subsample of the Israeli National Health Survey evaluated at baseline and after 7 years by identical protocols. Metabolic parameters and ultrasonographic evidence of NAFLD were evaluated in 213 subjects, without known liver disease or history of alcohol abuse. Exclusion criteria were pre‐DM at the baseline survey. Steatosis was quantified by ultrasound with the hepato‐renal ultrasound index (HRI). Results: The study included 141 volunteers (mean age 48.78 ± 9.68, 24.82% with NAFLD) without pre‐DM/DM at baseline. Both NAFLD on regular US (OR=2.93, 1.02–8.41 95%CI) and HRI (OR=7.87, 1.83–33.82) were independent predictors for the development of pre‐DM, adjusting for age, gender, BMI, family history of DM, baseline insulin, adiponectin and glucose. Further adjustment for physical activity and dietary intake did not weaken the association. Furthermore, NAFLD was a stronger predictor for pre‐DM than the metabolic syndrome. Subjects with both NAFLD and glucose ≥89 had 93.3% incidence rate of pre‐DM. Conclusion: Non‐alcoholic fatty liver disease is a strong and independent risk factor for pre‐DM in the general adult population; thus, NAFLD patients should be classified as a population at risk.